Evaluation of Internal Auditors' Role as Trusted Advisors to providing added value for organization - Liyana Rachmayanti; Dwi Martani (AFRE (Accounting and Financial Review), 2025)
This study aims to evaluate the role of PPATK's internal audit trusted advisor using Richard F. Chambers' trusted advisor attributes and the added value provided. This research uses a qualitative approach with a case study method. The results showed that the fulfillment of six attributes optimally, the role of internal auditors as trusted advisors can be said to be quite strong, although there are still three attributes (result focused, inspirational leaders, and technical expertise) that need to be optimized. This study also reveals the importance of improving soft and hard skills, as well as communication skills in improving their role as trusted advisors. In addition, this study also shows that internal auditor advisory has provided added value in five aspects (better decision-making processes, efficiency and effectiveness, risk management, strengthening internal controls, and compliance with regulations), although it has not been evenly distributed to all aspects and all supervision clients. This study implies that although respondents' perceptions have shown that internal auditors have acted as trusted advisors, it is necessary to evaluate the scope of advisory activities, and the added value generated. With a broader scope, internal auditors can further enhance their role and provide added value in more strategic areas. JEL Classification: Е24; Е41; Е64 DOI: https://doi.org/10.26905/afr.v8i1.14764